CONTEMPORARY APPROACH TO DIAGNOSIS OF GENETIC CAUSES OF INTELLECTUAL DISABILITY - Ana PETERLIN (Journal of Special Education and Rehabilitation, 2016)
Intellectual disability is a lifelong debilitating developmental disorder with important genetic contribution, which remains challenging to investigate due to high clinical and genetic variability. Finding the etiologic diagnosis of ID, however comes with great benefits for patients and their families, therefore establishing a genetic diagnostic pathway with right combination and succession of diagnostic tools is crucial for both prevention and appropriate treatment and/or rehabilitation of patients with ID. New diagnostic tools in genetics such as array comparative genomic hybridization (aCGH) and next-generation sequencing (NGS) have much higher detection rate for genetic aberrations responsible for ID and have enormous potential to shorten the path to diagnosis, as early diagnosis is a cornerstone for medical and non-medical management of persons suffering from ID.